EVALUATION OF BODY MEASUREMENTS FOR THE SELECTION OF LAMAS AND THEIR BABIES - Leyva V., Víctor (2007)
Lamas and their babies from the IVITA Research Center of San Marcos University were used to evaluate the body weight (BW), thoracic perimeter (TP), measures of thigh (TH), rump (RU) and udder, and milk yield, through correlation test to determine the suitable phenotype indicators for the selection of animals for meat production. The evaluation included the effect of age and parity of the dams from previous years using the ANOVA analysis. In the thigh was measured the length (LTH) and the circumference of its upper (CSTH) and lower (CITH) perimeter and, on the rump, the distance between its medial, lateral, sacral and coxal tuberosities. In the udder was measured the length, width and perimeter of the area between teats (PAT). The milk yield was weekly recorded until week seven of lactation and simultaneous to these measures was obtained the body weight of both mothers and babies. There were age and parity effects on TP and udder measurements; however, only the former effect was evident on thigh measurement. There was a significant relationship (high and mediun) of BW with TP, udder width and PAT with all thigh and rump measurements. Milk yield was not affected by age and parity, however had a clear relationship with udder width (p<0.0l) and PAT (p<0.l). In babies was found a high and significant relationship of BW with age and TP, LTH with CSTH and CITH while had an inverse relationship with age. In the mother-baby interaction, parity, age, BW, udder width, PAT and mother milk yield had positive relationships with baby BW; similar pattern had with TP, with the exception of parity and age, even with mother PT, CSTH and CITH. The CSTH and CITH and length of baby thigh had only a mediun relationship with udder measurements. In conclusion, the variables associated with milk yield (length and width of the udder and the PAT) were the most important to determine BW of baby lamas, which allow the selection of lama mothers to produce babies of high phenotypic value. The variables BW of the mother and the CSTH and CITH must be considered to select superior animals.